Kegiatan Fisioterapi Komunitas Mengenai Gambaran Pengetahuan Disminore Pada Siswi SMP Mutiara Harapan Lawang - Peluw, Kurnia Izza Habiba (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2025)
Adolescence is a time full of change. The first stage that marks maturity or puberty in girls is experiencing onset or menstruation. Menstruation, or what is better known as menstruation, is the shedding of the uterine wall, which consists of blood and body tissue (Fatmawati et al., 2016). Another definition can also be interpreted as a natural cycle that occurs regularly to prepare a woman's body every month. The average woman's menstrual period is 3-8 days, with an average cycle of 28 days each month. Every woman experiences different experiences. Some women experience menstruation without any complaints, but quite a few of them experience menstruation with complaints, causing discomfort in carrying out an activity. One of the complaints during menstruation is dysmenorrhea, which occurs during menstruation or after menstruation. Based on the results of the pre-test and post-counseling, there were significant differences regarding the knowledge of female students at Mutiara Harapan Lawang Middle School